USING OF IRON-CONTAINING WASTE OF RUP «BMZ» AS SECONDARY MATERIAL RESOURCES - D. M. Kukuj; L. E. Rovin; V. A. Matochkin; T. N. Lipatkina; S. L. Rovin (Литьë и металлургия)
Theoretical calculations on possibility of realization of the iron-carbon alloys recovery and production are given.